Research methods in educational leadership and management - Briggs, Ann R. J.; Coleman, Marianne; Morrison, Marlene (Sage, 2012)
This classic guide continues to be the leading Research Methods text that specifically deals with Educational Leadership and Management. The collection boasts an array of high profile international expert contributors, covering a wide range of specialisms, emphasizing the importance of the critically engaged practitioner.